Interactive advertising on products pharmaceuticals for human use: the phenomenon of autoregulation (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
On the Internet, many goods and services are advertised. In this sense, electronic promotion may have as an objective drugs intended for human use or consumption.In Spain, notwithstanding that the Web has a global reach, different rules have beenapproved to protect users from fraudulent or even harmful behaviors that can havefatal consequences in this area. Now, taking into account its inherent limitations,the pharmaceutical industry itself has been self-regulated, and suggestive codes ofconduct about it have been developed.
Keywords: self-regulation; pharmacy; advertising.